Determination of loading of computer complex of air traffic control system - Жуков I. А.; Дрововозов В. I.; Карпушин, Ю. П. (Proceedings of National Aviation University (archive), 2000)
Considered are the characteristics of functioning and loading of computer complex for air traffic control system in the process of running planning